Electronic commerce maturity: a review of the principal models - Morais, Elisabete Paulo (2007)
It has been more than three decades since Nolan proposed his stages of growth model for information systems. Since then several studies on the stages of growth theory appeared in the academic literature. Since models oriented to the management and planning of information systems even models oriented to the development of information systems. But the object of this article is to present the most cited maturity models for the electronic commerce or electronic business and compare them. This comparison will be made using a comparative framework to evaluate electronic business stages of growth models, illustrating perspective, development, emphasis, verification, focus, source, barriers to growth and number of stages.